Conversational marketing : how the world's fastest growing companies use chatbots to generate leads 24/7/365 (and how you can too) - Cancel, David, 1972-; Gerhardt, Dave, 1987- (Gildan, 2019)
Real-time conversations turn leads into customers Conversational Marketing is the definitive guide to generating better leads and closing more sales. Traditional sales and marketing methods have failed to keep pace with the way modern, internet-savvy consumers purchase goods and services. Modern messaging apps, which allow for real-time conversations and instant feedback, have transformed the way we interact in our personal and professional lives, yet most businesses still rely on twentieth-century technology to communicate with twenty-first-century customers. Online forms, email inquiries, and follow-up sales calls don't provide the immediacy that modern consumers expect. Conversational marketing and sales are part of a new methodology centered around real-time, one-on-one conversations with customers via chatbots and messaging. By allowing your business to communicate with customers in real time-when it's most convenient for them-conversational marketing improves the customer experience, generates more leads, and helps you convert more leads into customers. Conversational Marketing pioneers David Cancel and Dave Gerhardt explain how to merge inbound and outbound tactics into a more productive dialog with customers and integrate conversational marketing techniques into your existing sales and marketing workflow.